2020
DOI: 10.1097/iae.0000000000002418
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics and Visual Acuity of Highly Myopic Eyes With Different Severities of Myopic Maculopathy

Abstract: Purpose: To investigate the morphological feature, visual acuity, and prevalence of macular complications in highly myopic eyes with different categories of myopic maculopathy (MM) according to the META-PM classification system. Methods: The clinical records of 1,132 consecutive patients (1,841 eyes) with high myopia (refractive error ≤ −6D and axial length ≥26.5 mm), who visited the High Myopia Clinic at the Zhongshan Ophthalmic Center from January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 21 publications
5
54
1
3
Order By: Relevance
“…11,12,21 Patchy atrophy and macular atrophy may be different types of MM rather than a relationship of progress. 23 We also found some CNV-related macular atrophy eyes in which the atrophic lesion was limited, and no obvious atrophic changes were found around the lesion. Hence, in these cases it may be inappropriate to classify macular atrophy into the atrophic group.…”
Section: This Study Is To the Best Of Our Knowledge The Firstmentioning
confidence: 51%
See 1 more Smart Citation
“…11,12,21 Patchy atrophy and macular atrophy may be different types of MM rather than a relationship of progress. 23 We also found some CNV-related macular atrophy eyes in which the atrophic lesion was limited, and no obvious atrophic changes were found around the lesion. Hence, in these cases it may be inappropriate to classify macular atrophy into the atrophic group.…”
Section: This Study Is To the Best Of Our Knowledge The Firstmentioning
confidence: 51%
“…Several studies had reported a negative correlation between mChT and MM severity. 23,31 The thinning of choroidal thickness may contribute to various myopic pathologic changes, such as chorioretinal atrophy, LCs, and CNV. 20,[32][33][34][35] However, the definition of MM in these studies was based on atrophic and neovascular changes, and there are no studies reporting a correlation between choroidal thinning and myopic tractional changes.…”
Section: This Study Is To the Best Of Our Knowledge The Firstmentioning
confidence: 99%
“… 33 , 37 The first study was performed in a very young population, Singaporean men aged 19 to 25 years, and the second study was performed in asymptomatic Chinese patients aged 18 years and older, possibly explaining the low prevalence. 33 , 37 The study of Zhao et al 36 included the most myopic and oldest participants of which 96.9% had at least a tessellated fundus, and 54.5% also had diffuse, patchy, or macular atrophy.…”
Section: Resultsmentioning
confidence: 99%
“…34 The appearance of Fuchs spot is positively correlated with the severity of maculopathy from Category 0 to Category 4. 103 In highly myopic adults, the prevalence of Fuchs spot was moderate, with a study reporting 14.5 per cent prevalence in highly myopic adults. 42 The Handan study reported that Fuchs spot was less prevalent (14.3 per cent) when compared to other lesions such as staphyloma (86.9 per cent), chorioretinal atrophy (56 per cent) and lacquer crack (36.9 per cent).…”
Section: Fuchs Spotmentioning
confidence: 98%